2022
DOI: 10.1371/journal.pone.0271307
|View full text |Cite
|
Sign up to set email alerts
|

The effect of levocarnitine supplementation on dialysis-related hypotension: A systematic review, meta-analysis, and trial sequential analysis

Abstract: Background Dialysis patients have been shown to have low serum carnitine due to poor nutrition, deprivation of endogenous synthesis from kidneys, and removal by hemodialysis. Carnitine deficiency leads to impaired cardiac function and dialysis-related hypotension which are associated with increased mortality. Supplementing with levocarnitine among hemodialysis patients may diminish incidence of intradialytic hypotension. Data on this topic, however, lacks consensus. Methods We conducted electronic searches i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Chewcharat et al (17) reported secondary outcomes and showed that LC did not substantially reduce the symptoms of IH (P = 0.5; I2 0%, Pheterogeneity 0.83). Pre-HD BP (mmHg) SBP p value 0.85 DBP p value 0.75, as demonstrated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Chewcharat et al (17) reported secondary outcomes and showed that LC did not substantially reduce the symptoms of IH (P = 0.5; I2 0%, Pheterogeneity 0.83). Pre-HD BP (mmHg) SBP p value 0.85 DBP p value 0.75, as demonstrated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Levocarnitine supplementation, with or without exercise, could improve muscle cramps in patients with liver cirrhosis [ 12 , 13 , 40 ]. Regarding the dose and duration of levocarnitine supplementation, a dose of more than 4200 mg/week and with a duration of at least 12 weeks seemed to prevent dialysis-related hypotension [ 41 ]. Most of the total body carnitine is found in skeletal muscle, with 2–3% in the liver and kidney [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…The use of L-carnitine, a nutritional supplement that converts fatty acids to energy or online hemodiafiltration, as a convective blood purification technique to prevent IDH remain controversial strategies. 65 , 95 , 96 However, large trials that are increasingly unlikely to be funded in the era of shrinking resources limit the strong recommendation in prevention of IDH. More recently, machine-based learning methods now offer a fresh and potentially unbiased approach to tackling decades-old clinical problems.…”
Section: Researchmentioning
confidence: 99%